STUDYING THE EFFICIENCY OF SOME NANOPARTICLES ON SOME PLANT PATHOGENIC FUNGI AND THEIR EFFECTS ON HYPHAL MORPHOLOGY - S. A. Masoud,; A. R. Emara,; A. S. Mansy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was investigated the effect of iron NPs and essential oils of clove in normal and nanoemulsion forms for controlling Fusarium oxysporum, Fusarium solani, and Alternaria solani compared with Azoxystrobin fungicide under laboratory conditions. Data revealed that all tested compounds are capable of inhibiting the growth of mycelial of F. oxysporum F. solani, and A. solani from 0 to 84.4%, 0 to 88.9 %, and 0 to 61.1 %, respectively. There is relationship was found between the tested concentration of all treatments and their percentages of inhibition of mycelium. In addition, the use of Azoxystrobin, iron NPs and essential oils of clove in normal and nanoemulsion increased the activity of polyphenol oxidase (PPO). The fungal hyphae morphology was investigated by using scanning electron microscopy (SEM). The fungi hyphae without treatments are regular branching, linearly and normal morphology shaped, the surface of the hyphae is smooth and apical tapered. Treatments caused loss of linearity, irregular branching of the terminal hyphae, deformations of the hyphal shape, and the lysis cytoplasm of the hyphal.